Does mining fuel bubbles?: an experimental study on cryptocurrency markets - Lambrecht, Marco; Sofianos, Andis; Xu, Yilong (Discussion paper series, 2020)
Recent years have seen an emergence of decentralized cryptocurrencies that were initially devised as a payment system, but are increasingly being recognized as investment instruments.The price trajectories of cryptocurrencies have raised questions among economists and policy-makers, especially since such markets can have spillover effects on the real economy. We focus on two key properties of cryptocurrencies that may contribute to their pricing. In a controlledlab setting, we test whether pricing is influenced by costly mining, as well as entry barriers tothe mining technology. Our mining design resembles the proof-of-work mechanism employed by the vast majority of permissionless cryptocurrencies, such as Bitcoin. In our second condition, half of the traders have access to the mining technology, while the other half can only participate in the market. This is designed to model high concentration in cryptocurrency mining. In theabsence of mining, no bubbles or crashes occur. When costly mining is introduced, assets aretraded at prices more than 200% higher than fundamental value and the bubble peaks relativelylate in the trading periods. When only half of the traders can mine, prices surge much earlierand reach values of almost 400% higher than the fundamental value at the peak of the market. Overall, the proof-of-work mechanism seems to fuel overpricing, which is further intensified byconcentration in mining.